Respuesta :
Answer:
-x + 6 = 1 is the resulting equation when the expression for y in the second equation is substituted into the first equation 3x + y = 1 y = 6 - 4x . 5x = 10 is the result of adding the system of equations: 2x + y = 4 3x - y = 6 .Step-by-step explanation:
mark brainiest
Answer:
the ans is -5 hope it may help u
Step-by-step explanation:
first 3x +y =1
y = -3x +1
putting the value of y in other equation
y=3-4x
-3x+1 = 3 -4x
x = 2 putting the value of x in first equation
6 + y =1
so y =-5